Numerical Simulation of Irregular Breaking Waves Using a Coupled Artificial Compressibility Method - Athanasios Dermatis; Dimitrios Ntouras; George Papadakis (Fluids, 2022)
Wave breaking is widely recognized as a very challenging phenomenon to emulate using numerical/computational methods. On that condition, the transition from modelling regular to irregular breaking waves is not trivial. Even though some issues are surpassed in CFD simulations, there still are two substantial problems to account for. The first one entails the proper generation of irregular waves in a numerical wave tank, while the second is the introduction of the turbulent regime of breaking in the solver. The present work addresses these two problems by employing the Stabilized <semantics>k−ω</semantics> SST model for turbulence closure and by proposing an efficient and accurate method for irregular wave generation. Apart from that, an artificial compressibility method is used for coupling the system of equations, which solves these equations in a non-segregated manner and overcomes problems pertaining to the existence of the interface in free-surface flows. The methodology is validated through the test case of irregular wave propagation over a submerged breaker bar and a piecewise sloped bottom, indicating the ability of the method to capture irregular breaking wave phenomena. Simulations are in fair agreement with experimental data regarding energy spectra and free surface time-series, while results suggest that the known over-prediction of turbulent kinetic energy (TKE) is significantly constrained by the stabilized <semantics>k−ω</semantics> SST model.